2000
DOI: 10.1108/01443570010348262
|View full text |Cite
|
Sign up to set email alerts
|

TQM and business performance in the service sector: a Singapore study

Abstract: This paper focuses on gaining insight into the impact of TQM on the business performance of the service sector of the economy. The study yields clear evidence that TQM implementation improved business performance in the service sector of Singapore. Success of TQM implementations appears to be attributable more to the rigor of its implementation rather than the duration. The study finds that while accrued benefits can be attributed to some of the tools of TQM, such as, customer focus and quality improvement rew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
182
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(195 citation statements)
references
References 26 publications
2
182
1
Order By: Relevance
“…Some studies have suggested that TQM-adopting firms enjoy a competitive advantage over non-TQM (Powell 1995, Brah et al, 2000. Furthermore, numerous empirical studies, which attempt to examine the impact of TQM, support the proposition that a continuous commitment to TQM implementation has a significant positive effect on superior firm performance, as evidenced in the case of service firms (Agus, 2004), small and medium enterprises (Ahmad et al, 2014;Wali & Boujelbene, 2010;Salaheldin, 2009) and European companies (Boulter et al, 2013).…”
Section: Relationship Between Organizational Learning Tqm and Businmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have suggested that TQM-adopting firms enjoy a competitive advantage over non-TQM (Powell 1995, Brah et al, 2000. Furthermore, numerous empirical studies, which attempt to examine the impact of TQM, support the proposition that a continuous commitment to TQM implementation has a significant positive effect on superior firm performance, as evidenced in the case of service firms (Agus, 2004), small and medium enterprises (Ahmad et al, 2014;Wali & Boujelbene, 2010;Salaheldin, 2009) and European companies (Boulter et al, 2013).…”
Section: Relationship Between Organizational Learning Tqm and Businmentioning
confidence: 99%
“…The second part contains 19 items on the subject"s cognition of the implementation of TQM by the non-life insurance company. This study is based on the characteristics of the non-life insurance companies and through a comprehensive review of the TQM literature, with four constructs of TQM practices, named customer focus (Oakland, 2005;Fotopoulos & Psomas, 2010;Phan et al, 2011), continuous improvement (Tsang & Anltony, 2001;Wang et al, 2012 ), process management (Brah et al, 2000;Sila & Ebrahimpour, 2005;Samat et al, 2006) and service culture (Sureshchander et al, 2001;Selvaraj, 2009) to represent the core of TQM practices which are found to be useful and relevant to the service industries (Brah et al, 2000;Tsang & Antony, 2001). The third part contains 10 items on the impact of the implementation of organizational learning and TQM on the firm"s business performance, which according to Hao et al (2012) divide into two constructs including financial performance (e.g., Premium revenues, profit after tax, cost improvement) and non-financial performance (e.g., market share, customer satisfaction, employee productivity).…”
Section: Questionnaire Design and Measures Of Constructsmentioning
confidence: 99%
“…The growth of service sector is due to the fact that service organizations cover a broad spectrum [2]. They interact directly with large number of customers.…”
Section: IIImentioning
confidence: 99%
“…Dimensions and measurements have been adopted and adapted from previous studies. ERP measurements have been adopted from Stratman and Roth (2002), whereas measurements of TQM from different sources: Brah, Wong, and Rao (2000), Anderson and Sohal (1999), Terziovski & Samson (1999), and Rao (2000). Measurements of organizational excellence have been adopted from Pinar and Girard (2000), and organizational performance from Kaplan and Norton (1992;.…”
Section: Methodsmentioning
confidence: 99%